A novel robust generalized backstepping controlling method for a class of nonlinear systems. Issue 1 (1st January 2017) - Ghanavati, Malek; Salahshoor, Karim; Jahed Motlagh, Mohammad Reza; Ramezani, Amin; Moarefianpour, Ali
Abstract: This study is aimed at introducing a new robust control strategy in developed backstepping method designed for a special class of nonlinear systems, which does not require any information on the upper bound of parametric uncertainties. A robust generalized backstepping method (RGBM) is introduced by using of both generalized backstepping method and nonlinear damping of Lyapunov redesign. The RGBM is more efficient than the standard backstepping method because the standard backstepping method can only be applied to strictly feedback systems while RGBM expands this class. In addition, RGBM has could be applied to a special class of nonlinear systems with unmatched uncertainty and unknown upper bound. Numerical simulations demonstrate the feasibility and advantages of the proposed algorithm. Finally, the compressor surge control system is reviewed to show the robustness of the proposed scheme.